1991
DOI: 10.3109/00365519109104620
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Tumor-Associated Trypsin Inhibitor (Tati) in Benign and Malignant Gynecological Diseases

Abstract: Torre GC, Rembado R, Barbetti V, Vigliercio GP, Foglia M, Calabrese A, Corongiu F. Serum levels of tumor-associated trypsin inhibitor (TATI) in benign and malignant gynecological diseases. Scand J Clin Lab Invest 1991; 51 (Suppl. 207): 15-18.The behavior of tumor-associated trypsin inhibitor (TATI) as a marker for gynecological cancer was studied in a control population and in patients with different benign and malignant diseases. When a cut-off level of 21.4 pgll was used the specificity was 100% in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Osteopontin, a N-linked glycoprotein family of calcified extra-cellular matrix–associated protein, has been discussed as a potential diagnostic biomarker for ovarian cancer and showed evidence of an association between levels of osteopontin in serum and ovarian cancer suggesting that it would be worthwhile for future research assessing its clinical usefulness (Kim et al 2002; Bramwell et al 2006). Tumor-associated trypsin inhibitor’s elevated level is another important predictor of disease stage and future prognosis in ovarian cancer (Torre et al 1991). Moreover, a study suggested that preoperative serum Human Chorionic Gonadotropin-beta is a strong independent prognostic factor in epithelial ovarian carcinoma (Higashida et al 2001) when measured with a sensitive and specific method (Vartiainen et al 2001).…”
Section: Biomarkers In Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopontin, a N-linked glycoprotein family of calcified extra-cellular matrix–associated protein, has been discussed as a potential diagnostic biomarker for ovarian cancer and showed evidence of an association between levels of osteopontin in serum and ovarian cancer suggesting that it would be worthwhile for future research assessing its clinical usefulness (Kim et al 2002; Bramwell et al 2006). Tumor-associated trypsin inhibitor’s elevated level is another important predictor of disease stage and future prognosis in ovarian cancer (Torre et al 1991). Moreover, a study suggested that preoperative serum Human Chorionic Gonadotropin-beta is a strong independent prognostic factor in epithelial ovarian carcinoma (Higashida et al 2001) when measured with a sensitive and specific method (Vartiainen et al 2001).…”
Section: Biomarkers In Serummentioning
confidence: 99%
“…In systemic malignant melanoma, melanoma-inhibiting activity was found to represent a serum marker for this cancer showing a high sensitivity and specificity (Bosserhoff et al 1997). A studying group have discussed human chronic gonadotropin-beta as being most commonly elevated (>10 mIU/ml) in the serum of gynecological cancers especially ovarian cancer (Higashida et al 2001), but it is also elevated in colorectal (Lundin et al 2000), pancreas (Syrigos et al 1998), and kidney (Torre et al 1991), cancers and, therefore, can be referred to as a “current serum cancer marker.” D-dimer’s elevated levels in serum, a fibrin degradation product, has also been proposed as an important prognostic biomarker for metastatic colorectal carcinoma (Blackwell et al 2004) but its use is limited by its low specificity. CEA is reported as a colon cancer marker having low specificity and insufficient sensitivity to be used as a screening marker, as it can be elevated by many other factors than cancer; smoking for instance raises CEA levels, but can be helpful in follow-up (Bast et al 1996; Chatterjee and Zetter, 2005).…”
Section: Biomarkers In Serummentioning
confidence: 99%